Assessment of urbanization-induced ecological risks in an area with significant ecosystem services based on land use/cover change scenarios. Issue 5 (4th July 2018) - Liao, Jiangfu; Jia, Yuqiu; Tang, Lina; Huang, Qiaoling; Wang, Yangyang; Huang, Ning; Hua, Lizhong
ABSTRACT: Ecosystem services are facing numerous potential threats in rapidly developing areas. In this study, we investigated land use/cover change scenarios related to ecological risks due to urban development in an area with significant ecosystem services. Expansion of developed areas was considered as a risk source, and regional ecosystem services, such as soil conservation, soil erosion, and water conservation, were considered as risk receptors. Xiamen City was selected as a study case. Land-use and land-cover change processes in the study area were analyzed and used to predict future changes in urban spatial morphology. The analytic hierarchy process and ordered weighted averaging methods were employed to evaluation of urban comprehensive ecological risk and corresponding risk scenario settings. Most of northern and southern Xiamen City displayed a high level of ecosystem service under various high- or low-risk scenarios. Under the high-risk scenario, the average values of ecological risk due to newly developed land and total developed land were 0.402 and 0.324, respectively, in 2030 (power function exponent = 0.1). The average value of ecological risk due to newly developed land was generally higher than that caused by total developed land. In some local areas, such as Maluanwan and the small watershed Houxi, the ecological risk due to newly developed land was two to three times the average value for the entire study area. The results of this study provide an important reference for urban development.